Studies on emotional aspects in the design of user interfaces - Bianchi, Renata Germano (Universidade Federal de São Carlos, 2016)
Emotions play a crucial role in the way people interact with each other, objects and computing systems, and are a key factor in human-computer interaction. The choice of the appropriate elements for a user interface may result in a better experience of how it can be used. However, most studies investigate people’s preferences and visual aesthetics, without taking into account people’s emotion in the design. This dissertation carries out a series of detailed studies on the emotional effects of user interface elements, by examining colors, fonts and images. A critical analysis of the literature (through a systematic review) combined to the Semantic Space of Emotions, which covers a broad spectrum of emotions, resulted in the proposal of Bianchi’s Color Wheel. An empirical study was conducted on the emotional effects of font types and sizes; this involved 60 users and was necessary because there are so few studies on fonts and emotions in the literature. With regard to font types, in statistical terms, it was found there were no significant differences, although Arial was more closely linked to positive emotions than Times New Roman in the discourse analysis. Small font sizes, 8pt, caused negative experiences and led to tiredness, while medium (12pt) and large (16pt) sizes were mainly related to pleasant and comforting experiences. The third study investigated tagged and felt emotions evoked by images which were collected through social tags that were clearly related to emotions. The aim of the study was to determine whether or not these images are reliable for the design and retrieval. Thus, an online survey was planned and carried out by a group of 410 volunteers who classified pictures from Flickr. The results suggested that there are some emotions tagged that were similar to observers emotions, while others are diffuse and need other criteria for their selection apart from social tags. Finally, it should be mentioned that further studies are needed to address the complete user interface with all these elements and findings combined.
Keywords: Emoção; Interação humano-computador; Indexação coletiva; Imagens; Design; Emotion; Human-computer interaction; Social tagging; Pictures; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO